Morbility due to tuberculosis: epidemiological, clinical and diagnostic aspects. Santiago de Cuba. 2007-2011 - Làzaro Ibrahim Romero Garcìa; Pedro Alexei Bacardì Zapata; Yordanys Paez Candelaria; karima Maricel Gondres Legró; Digna de la C. Bandera Jiménez (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and cross-sectional study of the 323 cases with confirmed diagnosis of tuberculosis was carried out in  Santiago de Cuba, aimed at characterizing the incidence of this disease during 2007-2011, for  which the percentages and the typified  incidence rates  were calculated.  Among the main results  prevailed:  Mella municipality  with the higher rate of incidence, the 25-34 years patients and the male sex;  also, 8 out of 10 sick persons presented lung tuberculosis (81.0%) and the diagnostic procedure mostly used was the microscopic exam of sputum (56.6%). It is concluded that the incidence of this disorder in the territory is markedly higher with less favorable life conditions, and that the male sex and the lung tuberculosis were the most important epidemiological characteristics. The poor performance  in the realization of the baciloscopy for the diagnosis of this clinical entity in the studied population was observed.